2020
DOI: 10.3389/fcell.2020.00389
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in Embryogenesis and Cell Differentiation With a Focus on Cancer Development

Abstract: In the recent years thousands of non-coding RNAs have been identified, also thanks to highthroughput sequencing technologies. Among them, circular RNAs (circRNAs) are a well-represented class characterized by the high sequence conservation and cell type specific expression in eukaryotes. They are covalently closed loops formed through back-splicing. Recently, circRNAs were shown to regulate a variety of cellular processes functioning as miRNA sponges, RBP binding molecules, transcriptional regulators, scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 132 publications
(158 reference statements)
0
25
0
Order By: Relevance
“…CircRNAs can be transferred into cells by various delivery techniques, such as exosomes or viroid. Artificially constructing and transporting specific circRNAs into target cells can affect the communication between normal cells and tumor cells in the carcinogenesis process, and some experiments have already shown promising results [147]. In osteosarcoma patients, circ-0000190 was downregulated in extracellular nanovesicles and tissues, which could be utilized to distinguish osteosarcoma patients.…”
Section: A Perspective On Circrna In Cancer Therapymentioning
confidence: 99%
“…CircRNAs can be transferred into cells by various delivery techniques, such as exosomes or viroid. Artificially constructing and transporting specific circRNAs into target cells can affect the communication between normal cells and tumor cells in the carcinogenesis process, and some experiments have already shown promising results [147]. In osteosarcoma patients, circ-0000190 was downregulated in extracellular nanovesicles and tissues, which could be utilized to distinguish osteosarcoma patients.…”
Section: A Perspective On Circrna In Cancer Therapymentioning
confidence: 99%
“…Due to its stable, conserve, and spatio-temporal specificity futures, circRNAs are abundantly expressed in human tissues, and involved in various cellular progression [ 6 , 7 ]. In the past decades, the functions of circRNAs in multiple biological progressions have been deeply studied, including cervical cancer [ 8 – 11 ]. Gao et al revealed that has_circ‐0018289 mediates cervical cancer cell proliferation, invasion, and migration via acting as a molecular sponge for miR-497 [ 12 ], Song T et al elucidated the role of hsa_circRNA_101996 in cervical cancer development through regulating miR-8075/TPX2 axis [ 13 ], Tang Q et al demonstrated that hsa_circ_0000515 mediates cervical cancer progression via miR-326/ELK1 pathway [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different from linear RNA(with 5′ and 3′ ends), and circRNA molecule has a closed circular structure, that is not affected by RNA exonuclide, and its expression is more stable and not easy to degrade ( Dong et al, 2020 ; Jin et al, 2020 ; Zhang et al, 2020a ). In terms of functions, recent studies reveal that circRNA molecules are rich in microRNA (miRNA) binding sites, and act as a miRNA sponge in cells, thereby removing the inhibition of miRNA on its target genes and increasing the expression level of target genes ( Di Agostino et al, 2020 ; Li and Wang, 2020 ; Liu et al, 2020 ). This mechanism of action is called competitive endogenous RNA (ceRNA) mechanism.…”
Section: Introductionmentioning
confidence: 99%